Cover Feature: Bioinspired Mesoporous Chiral Nematic Graphitic Carbon Nitride Photocatalysts modulated by Polarized Light (ChemSusChem 1/2018). Issue 1 (27th December 2017) - Lin, Wensheng; Hong, Wei; Sun, Lu; Yu, Di; Yu, Dingshan; Chen, Xudong
Abstract : The Cover Feature shows the chiral nematic graphitic carbon nitride with photocatalytic activity modulated by circularly polarized light. In their work, the authors synthesized mesoporous g‐C3 N4 materials for photcatalytic hydrogen evolution. More information can be found in theCommunication by Lin et al onpage 114 in Issue 1, 2018 (DOI:10.1002/cssc.201701984 ).